Автодинные характеристики стабилизированных СВЧ-генераторов при сильном отраженном сигнале - Noskov, V. Ya.; Ignatkov, K. A.; Smolskii, S. M. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
Calculations and examinations of phase, amplitude, frequency and amplitude-frequency characteristics are fulfilled for the autodyne system stabilized by the external high-Q cavity as well as spectral characteristics under condition of exact and non-exact cavity tuning and the variations of distance to reflector. The distinguished peculiarities of the autodyne response at the small and large reflected signal are described. Experimental research results are discussed fulfilled on an example of the hybrid-integrated oscillator on Gunn diode of 8-mm-range, which confirm qualitatively the theoretic results.